Academic-industry partnership framework of Mariano Marcos State University - Robert A. Salvador; Cherrypn B. Barbacena; Francisco D. Esponilla II (International Journal of Evaluation and Research in Education (IJERE), 2021)
Higher education is a window for people to gain knowledge and skills. People who step out in higher academic learning are expected to be equipped with competencies needed in the different job sites. Therefore, the responsibility of every institution to seek alternatives to further enhance academic opportunities. The main objective of this study was to develop an academic-industry partnership (AIP) framework for the Mariano Marcos State University (MMSU). A qualitative research design was utilized in exploring the partnership engagement of the different colleges of the university. Interviews inquiring about participants' lived experiences were purposively selected for a grounded-theory analysis following the thematic coding process. The coding was further subjected to a triangulation for purposes of validating the data from various sources. The study revealed that the AIP is focused on the areas of instruction, research and production, and research and extension. This leads to the creation of the AIP framework which can contribute to the development of AIP policy of the MMSU and other higher education institutions.